Comparative Study of Education Systems in Canada and Indonesia - Tuerah, Paulus Robert; Nonis, Nonis; Mesra, Romi (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2024)
Education serves as a catalyst for national development, shaping the knowledge and skills of future generations. This comparative study examines the education systems of Canada and Indonesia, two nations with distinct cultural, geographical, and historical contexts. Through a comprehensive analysis, it contrasts the governance structures, curricula, language policies, and resource allocation strategies employed by these countries in their pursuit of quality education. Employing a qualitative research methodology, this study conducts an extensive literature review and document analysis to explore the unique challenges and opportunities faced by each nation's education system. The decentralized model adopted by Canada allows for regional adaptations while maintaining nationwide standards, whereas Indonesia's centralized approach promotes unity and cohesion across its archipelagic landscape. Particular emphasis is placed on investigating the overarching educational goals and priorities set forth by Canada and Indonesia, illuminating the underlying values, ideologies, and societal aspirations that shape their respective systems. The study delves into the competencies and skills prioritized, the preparation of students for future roles, and the integration of social, cultural, and indigenous considerations into the educational frameworks. By juxtaposing these contrasting approaches, the research uncovers valuable insights into the strengths and limitations of each model, as well as potential areas for cross-pollination of effective practices. The comparative nature of this study transcends geographic and cultural boundaries, fostering a broader understanding of the diverse pathways nations undertake to ensure accessible and effective education.